Bone copper content in sheep in relation to their drinking water source - Castellanos Ruelas, Arturo; Rosado-Rubio, J. Gabriel; Betancur-Ancona, David A.; Heredia-y Aguilar, Manuel (Ecosistemas y Recursos Agropecuarios, 2017)
The aim was to estimate the Cu content in the bones of grazing sheep and relate it to their drinking water. Cu was analyzed by taking bone biopsies. Samples from the twelfth rib were taken in 107 animals and water samples were collected from forty wells in the same farms located in four agroecological areas in Yucatán state, Mexico. Cu was analyzed by atomic absorption. Data were analyzed using the least squares method. Cu content in bone tissue was: weaned 0.66 a; Females prior to rst gestation 0.57b and ewes 0.64a mg/kg-1. Normal content in bone is 2-3 mg/kg-1, indicating a de ciency in the animals. Cu in water was 0.15 ab, 0.12 b, 0.16ab and 0.19a mg/L-1 in the center, east, west and south part of the State respectively. Cu concentration in water for animal consumption was low. In conclusion, Cu de ciency was diagnosed in grazing sheep that could be associated with the low Cu content in the drinking water.
Keywords: microminerals; grazing; tropics; mineral requirements; hair sheep